THE STATE OF THE BULGARIAN RAILWAY TRANSPORT AND THE PERSPECTIVES OF ITS FURTHER DEVELOPMENT - Ivanova, Lyubov (Revista Inclusiones, 2020)
In August 2018 Bulgaria marked the 130th anniversary of the existence of the Bulgarian State Railways. Тhe rail transport has a huge and rich historical role and has always been the backbone of the national transport system. Unfortunately, today it has been subjected to difficult trials. Bulgaria has a strategic position, situated between Turkey and Western Europe and has a key role on the Balkans. From a geographical point of view, the country offers a huge resource for railways, for the expansion of the transport links and for the realization and significant growth of transport and revenues. Rail services are at risk and in crisis, and forecasts show that, instead of developing upward, rail continues to operate with damping functions. The demand for rail services is declining and this has led to very low freight volumes and a significant drop in the own revenues. The railways were left without authority in the business and the civil society. The railways play a key role in the transport services market in, and through Bulgaria, and they must be seen as a strategic partner for the modernization of the transport service.